THE DIAGNOSTIC VALUE OF MAGNETIC RESONANCE IMAGING IN SUBACROMIAL IMPINGEMENT SYNDROME (Vietnam Journal of Community Medicine, 2021)
The retrospective study was performed on 45 patients with subacromial impingement syndrome who underwent magnetic resonance imaging (MRI) which then were compared with the results of their arthroscopy.Results: 95.2% out of the cases were found to have type II and III acromion morphology; 73.8% had subacromial enthesophyte spurs; 66.7% had subacromial bursitis; 97.6% showed lesions of supraspinatus tendons in which partial–thickness rotator cuff tear was the most commonly seen. MRI showed a sensitivity (Sn) of 91.6%, specificity (Sp) of 72.2%, positive predictive value (PPV) of 81.4%, negative predictive value (NPV) of 86.67% in diagnosing subacromial bursitis. For partial-thickness rotator cuff tear, it showed a Sn of 92.5%, Sp of 93.3%, PPV of 96.1%, NPV of 87.5%. In evaluation of full-thickness rotator cuff tear, MRI showed a Sn of 100% and Sp of 100%.
Keywords: MRI of the shoulder, subacromial impingement syndrome, rotator cuff tear